Evaluation of Deficit Irrigation and Water Quality on Production and Water Productivity of Tomato in Greenhouse - Jeet Chand; Guna Hewa; Ali Hassanli; Baden Myers (Agriculture, 2020)
This study deals with the evaluation of the effects of deficit irrigation (DI) and water quality (WQ) on the vegetative and productive response of greenhouse-grown tomatoes (Lycopersicon esculentum Mill. cv. Izmir). A pot-based experiment was carried out over two growing seasons. Three WQ: (groundwater, recycled wastewater and a mix of both) were applied in four irrigation scenarios which targeted soil moisture content (SMC) maintaining at 60%, 70%, 80% and 100% of field capacity (FC). Results showed that both DI and WQ had significant effects on crop development, yield and water productivity. The highest values of plant height (186.0 ± 0.58 cm) and stem diameter (23.40 ± 0.02 mm) were found at 100% FC (control). Total yield ranged from 2.33 ± 0.03 kg/plant (60% FC) to 4.05 ± 0.06 kg/plant (control). However, mild water stress (SMC maintaining at 80% FC) showed a positive effect on irrigation water use efficiency (IWUE) without significant yield reduction compared to control. IWUE was at its maximum (31.77 ± 0.47 kg/m3) at 80% FC. A DI regime based on 80% FC could be an efficient irrigation strategy particularly in water-limiting condition. Recycled wastewater was superior among the three WQ for achieving a better crop growth, yield and water productivity at same DI level.